HUBUNGAN ANTARA PRESEPSI GURU TENTANG GAYA KEPEMIMPINAN KEPALA SEKOLAH DENGAN SEMANGAT KERJA GURU DI SMP N 2 GEBANG KABUPATEN LANGKAT - Desi Anggraini (Universitas Islam Negeri Sumatera Utara Medan, 2018)
The purpose of this research is to know the: (1) the principal leadership style exist; (2) teachers morale lies; (3) a significant relationship between the perception of teachers about the leadership style of the principal with the morale of teachers. The subject is a Junior High School teacher 2 Gebang District of Langkat population 35 and sample as many as 32 people. Sampling is carried out by random sampling. The method research of korelasional which aims to menjelakan the relationship between the two variables. The results showed an average count variable style kepemimpianan of 37.5%; morale of 40,625%. Based on hypothesis testing follows the leadership style and are significantly associated with the morale of teachers in Junior High School 2 Gebang District of Langkat Ultraman hypothesis suggests that there is a relationship medium and significantly between the leadership style (X) and (Y) Morale, it is characterized with donations effectively amounted to 0.5%. While the value of relationship significance both (leadership style against the spirit of the work) can be seen through the test of ' t